2013
DOI: 10.1371/journal.pone.0074965
|View full text |Cite
|
Sign up to set email alerts
|

Isolation Associated Aggression – A Consequence of Recovery from Defeat in a Territorial Animal

Abstract: Population density has profound influences on the physiology and behaviour of many animal species. Social isolation is generally reported to lead to increased aggressiveness, while grouping lowers it. We evaluated the effects of varying degrees of isolation and grouping on aggression in a territorial insect, the Mediterranean field cricket, Gryllus bimaculatus . Substantiating early observations, we show that dyadic contests between weight-matched, adult male crickets taken from groups rarely escalate beyon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 74 publications
5
50
0
Order By: Relevance
“…There are at least two possible explanations for these results. Social isolation has been suggested to induce dominance-like status in different species including fish (45,46). If this is the case in zebrafish, than the behavioral state of winners is expected to be closer to that of socially isolated fish and that would explain the lower number of DE genes and gene modules in winners than losers, when using social isolation as a reference group.…”
Section: Gene Modules Inferred By Weighted Gene Coexpression Networkmentioning
confidence: 99%
“…There are at least two possible explanations for these results. Social isolation has been suggested to induce dominance-like status in different species including fish (45,46). If this is the case in zebrafish, than the behavioral state of winners is expected to be closer to that of socially isolated fish and that would explain the lower number of DE genes and gene modules in winners than losers, when using social isolation as a reference group.…”
Section: Gene Modules Inferred By Weighted Gene Coexpression Networkmentioning
confidence: 99%
“…Prior experience is another known predictor of future behaviours in many animal species (Hsu et al, 2006;Rutte et al, 2006;Seebacher & Wilson, 2007;Jeanson & Fewell, 2008;Wong & Balshine, 2011;Manfredini et al, 2013;Stevenson & Rillich, 2013), including social insects (van Doorn, 2008;Amsalem & Hefetz, 2010;Amsalem et al, 2013). The negative correlation between aggression and avoidance suggests two distinct behaviour outcomes, whereby those two behaviours are, in their extremes, mutually exclusive ( Figure 1).…”
Section: Social Experience Effectsmentioning
confidence: 99%
“…Loser and winner effects have been widely studied in many species, including insects (Stevenson and Rillich 2013), fish (Chase et al 1994), and mammals (Schwartzer et al 2013). Few studies, however, have reported such effects on Drosophila Cold Spring Harbor Laboratory Press on May 9, 2018 -Published by learnmem.cshlp.org Downloaded from (Yurkovic et al 2006;Penn et al 2010).…”
mentioning
confidence: 99%